THE STRATEGY OF PT. ASTRA HONDA MOTOR IN MAINTAINING COMPETITIVE ADVANTAGE SUSTAINABLY MOTORCYCLE - Rafsanjani, Sherva; Rifai, Emon (Universitas Trunojoyo Madura, 2025)
The motorcycle industry in Indonesia has been growing year after year, and consumers have a wide choice of Japanese and Chinese brands, which are aggressively promoting electric products. Based on sales figures from the Indonesian Motorcycle Industry Association (AISI), the Honda brand consistently dominates the market, achieving 80% market share and the highest sales growth over the past ten years. PT. Astra Honda Motor (AHM), as the Sole Brand Holder Agent (ATPM), implements a Sustainable Competitive Advantage (SCA) strategy: Positioning strategy through the product image of Honda motorcycles as high-tech, tough, fuel-efficient, with a wider range of product variants, and a trusted global brand. Distribution strategy through showrooms, authorized workshops, and spare parts outlets throughout Indonesia and relatively easy to find. A pricing strategy that sets prices quite high compared to competitors to demonstrate Honda's market leadership and product quality by providing assurance about its products.